Process evaluation of a randomised trial of a triple low-dose combination pill strategy to improve hypertension control: a qualitative study - Vanessa Selak; Anushka Patel; Anthony Rodgers; Stephen Jan; Dorairaj Prabhakaran; Abdul Salam; Lakshmi K Josyula; Nitish Naik; Pavithra Godamunne; Arunasalam Pathmeswaran; Tracey Laba; Rupasvi Dhurjati; et al. (BMJ Open, 2025)
Background High blood pressure (BP) is a significant global health issue, with many treated patients failing to achieve BP control. The Triple Pill vs Usual Care Management for Patients with Mild-to-Moderate Hypertension (TRIUMPH) trial evaluated the effectiveness, cost-effectiveness and acceptability of early use of low-dose triple fixed-dose combination of BP-lowering drugs (‘triple pill’) compared with usual care in the management of hypertension. The TRIUMPH trial showed superior BP control with the triple pill strategy compared with usual care. This process evaluation of the TRIUMPH trial aimed to explore the contextual factors that influenced the trial outcomes, implementation of the triple pill strategy, mechanisms of its effects and potential barriers and facilitators for implementing the triple pill strategy in routine practice.Methods Guided by the UK Medical Research Council’s framework, semistructured interviews were conducted with 23 patients and 13 healthcare providers involved in the TRIUMPH trial. Data were analysed using the framework analysis method in NVivo.Results Hypertension care in Sri Lanka was hindered by the absence of systematic screening and overcrowded public clinics. Despite free medication provision at public clinics, long waiting times and occasional stock-outs posed challenges. In the TRIUMPH trial, both intervention and usual care were delivered in the context of ‘better than usual’ care, including team-based management, reduced waiting times, monetary assistance for travel, routine adherence monitoring and intensive follow-up. The triple pill strategy provided a simplified regimen, better access to BP-lowering medications and better BP-lowering efficacy. Key barriers to implementation in routine practice included the triple pill’s large size, therapeutic inertia and restrictive regulatory policies regarding fixed-dose combinations.Conclusions Implementation of the triple pill strategy into routine practice requires health system strengthening, provider training and supportive policy measures to replicate its effectiveness seen in the trial.Trial registration number ACTRN12612001120864, SLCTR/2015/020.